KOMPARASI PERENCANAAN STRATEGIS (RENSTRA) KEMENDIKBUD DAN SMA NEGERI 68 JAKARTA BERDASARKAN ANALISIS TEORI - Dikson Silitonga (ESENSI: Jurnal Manajemen Bisnis, 2019)
A good vision and mission creation is vey important to formulate, implement and evaluate a strategy for the period to come. Without the clear statement of vision and mission, any short term activities of a company can become contra-productive for the long term interests. To achieve strategic goals, a number of strategic targets need to be set up in order to map out the condition that must be achieved. This research use a comparative method that is intended to compare two groups or more in a certain variable, namely to compare strategic plan between the Ministry of Education and Culture and the 68 Senior High School (SMA Negeri 68) of Jakarta. The technics of data collection used in this research are observation, interview, and library studies. Keywords: vision, mission, strategic plan, comparative, interview, library studies. A good vision and mission creation is vey important to formulate, implement and evaluate a strategy for the period to come. Without the clear statement of vision and mission, any short term activities of a company can become contra-productive for the long term interests. To achieve strategic goals, a number of strategic targets need to be set up in order to map out the condition that must be achieved. This research use a comparative method that is intended to compare two groups or more in a certain variable, namely to compare strategic plan between the Ministry of Education and Culture and the 68 Senior High School (SMA Negeri 68) of Jakarta. The technics of data collection used in this research are observation, interview, and library studies.